2017
DOI: 10.1007/s13197-017-2538-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of color, anti-nutritional factors, minerals, phenolic profile and protein digestibility between hard-to-cook and easy-to-cook grains from different kidney bean (Phaseolus vulgaris) accessions

Abstract: The present study was aimed to evaluate the differences among anti-nutritional factors in relation to mineral absorption and protein digestibility of Easy-tocook (ETC) and Hard-to-cook (HTC) grains from different kidney bean (KB) accessions.HTC grains showed lower a* (redness to yellowness) and b* (greenness to blueness) values and L* value than ETC grains. HTC grains had significantly higher Ca and Zn and lower Cu, Mn and Fe than ETC grains. ETC and HTC grains showed significant variation in mineral, total ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 45 publications
2
58
0
2
Order By: Relevance
“…Crude protein concentrations varied from 20.33 (black bean) to 24.94% (white and matte red kidney beans). Similar crude protein values (Saha et al, 2009;Parmar et al, 2017) or higher values (Pinheiro, Baeta, Pereira, Domingues, & Ricardo, 2010;Silva et al, 2012;Hacisalihoglu & Settles, 2013) were previously described for bean genotypes of different colours. However, Silva et al (2012) observed higher crude protein values in black bean genotypes, in contrast to the present study.…”
Section: Different Bean Colours and Their Nutritional Qualitysupporting
confidence: 79%
See 1 more Smart Citation
“…Crude protein concentrations varied from 20.33 (black bean) to 24.94% (white and matte red kidney beans). Similar crude protein values (Saha et al, 2009;Parmar et al, 2017) or higher values (Pinheiro, Baeta, Pereira, Domingues, & Ricardo, 2010;Silva et al, 2012;Hacisalihoglu & Settles, 2013) were previously described for bean genotypes of different colours. However, Silva et al (2012) observed higher crude protein values in black bean genotypes, in contrast to the present study.…”
Section: Different Bean Colours and Their Nutritional Qualitysupporting
confidence: 79%
“…Matte red kidney and shiny red kidney beans differed only by L values, and did not present variation in their a* and b* values. Similarly, Ribeiro et al (2014b) and Parmar, Singh, Kaur, and Thakur (2017) observed that kidney bean genotypes were different for grain luminosity (L value). However, Parmar et al (2017) found a large variation in the a* and b* values in grains of 11 kidney bean genotypes, probably due to the greater diversity of red shades in the samples evaluated.…”
Section: Different Bean Colours and Their Technological Qualitymentioning
confidence: 86%
“…Tannins have been described to have cross-linked with proteins and caused a reduction in in vitro protein digestion of beans [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…ey have also been implicated in the inhibition of digestive enzymes, increased excretion of endogenous protein, and effect on digestive tract [39].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolics are generally bound with cell wall structural proteins and carbohydrates (Parmar et al, 2017) and might get released by rupture of cell wall upon heating resulting in the increase in TPC of cookies. TPC of cookies might also be enhanced due to the generation of Malanoidins produced in the Maillard reaction at high temperatures (Bhat et al, 2018).…”
Section: Total Phenolic Content Of the Scg Cookiesmentioning
confidence: 99%